Conquering the cytokine storm in COVID‐19‐induced ARDS using placenta‐derived decidua stromal cells. Issue 22 (10th October 2021) - Sadeghi, Behnam; Roshandel, Elham; Pirsalehi, Ali; Kazemi, Sepide; Sankanian, Ghazaleh; Majidi, Mohammad; Salimi, Maryam; Aghdami, Nasser; Sadrosadat, Hoda; Samadi Kochaksaraei, Sarvenaz; Alaeddini, Farshid; Ringden, Olle; et al.
Abstract: Acute respiratory distress syndrome (ARDS) is the most common cause of death in COVID‐19 patients. The cytokine storm is the main driver of the severity and magnitude of ARDS. Placenta‐derived decidua stromal cells (DSCs) have a stronger immunosuppressive effect than other sources of mesenchymal stromal cells. Safety and efficacy study included 10 patients with a median age of 50 (range 14–68) years with COVID‐19‐induced ARDS. DSCs were administered 1–2 times at a dose of 1 × 10 6 /kg. End points were safety and efficacy by survival, oxygenation and effects on levels of cytokines. Oxygenation levels increased from a median of 80.5% (range 69–88) to 95% (range 78–99) ( p = 0.012), and pulmonary infiltrates disappeared in all patients. Levels of IL‐6 decreased from a median of 69.3 (range 35.0–253.4) to 11 (range 4.0–38.3) pg/ml ( p = 0.018), and CRP decreased from 69 (range 5–169) to 6 (range 2–31) mg/ml ( p = 0.028). Two patients died, one of a myocardial infarction and the other of multiple organ failure, diagnosed before the DSC therapy. The other patients recovered and left the intensive care unit (ICU) within a median of 6 (range 3–12) days. DSC therapy is safe and capable of improving oxygenation, decreasing inflammatory cytokine level and clearing pulmonary infiltrates in patients with COVID‐19.